Note for Soft MultiExpert Graph and MultiSoft MultiExpert Graph - Takaaki Fujita (Magister Program of Mathematics, Universitas Lampung, 2026)
This paper studies multilevel extensions of soft-set-based graph models for uncertainty aware decision support. We first recall soft, multisoft, soft expert, and multisoft multi expert sets, which encode parameterized and expert-dependent approximations of a universe. Building on these notions, we introduce the MultiSoft Graph, a family of induced subgraphs of a given graph indexed by multilevel parameter blocks, and show that it strictly generalizes classical soft graphs while inducing a canonical multisoft set on the vertex set. We then define Soft MultiExpert Graphs and MultiSoft MultiExpert Graphs, providing a unified framework that jointly handles graph topology, multiple parameters, and expert opinions.